Record of Semiotic Representation Using Geogebra: An Olympiad Training on Brazilian Students - Santiago, Paulo Vitor da Silva; Alves, Francisco Régis Vieira (Indonesian Journal of Science and Mathematics Education, 2022)
This study aims to compile and develop an international didactic situtation presented with an approach to the center of an arbitrary triangle in visual exploration in 2D and 3D format using GeoGebra software as a technology for modification and construction of Olympiad questions. The methodology used in this study is an exploratory qualitative which is described from a didactic sequence of Mathematics Olympiad which were held in four online meetings using Google Meet. The results show that this exercise can be used as a resource that will provide a level of learning for students through command and visualization of images that serve a broad view of the international Olympiad situation. International didactic situations can be applied by mathematics teachers both in training for national and international Olympiad and for classroom teaching. In summary, it is noteworthy that the dynamic records of semiotic representations stimulated by the use of GeoGebra software has great potential to encourage the progress of students’ representative geometric thinking, through the development of visualization, perception, and mathematical intuition. It is hoped that this work can serve as a pedagogical and methodological tool by teachers for various competencies.